Modulation of Adult Hippocampal Neurogenesis by Sleep: Impact on Mental Health - Navarro-Sanchis, Cristina; Brock, Olivier; Winsky-Sommerer, Raphaelle; Thuret, Sandrine (Frontiers in Neural Circuits, 2017)
The process of neurogenesis has been demonstrated to occur throughout life in the subgranular zone of the hippocampal dentate gyrus of several mammals, including humans. The basal rate of adult hippocampal neurogenesis can be altered by lifestyle and environmental factors. In this perspective review, the evidence for sleep as a modulator of adult hippocampal neurogenesis is first summarized. Following this, the impacts of sleep and sleep disturbances on hippocampal-dependent functions, including learning and memory, and depression are critically evaluated. Finally, we postulate that the effects of sleep on hippocampal-dependent functions may possibly be mediated by a change in adult hippocampal neurogenesis. This could provide a route to new treatments for cognitive impairments and psychiatric disorders.